Manifestações patológicas de revestimentos cerâmicos em fachadas:um estudo de caso do Teatro Municipal Dix-huit Rosado em Mossoró-RN - Carvalho, Francisca Evânia (Universidade Federal Rural do Semi-Árido, 2020)
Ceramic tiles are widely used in civil construction due to their various possibilities of application on floors and internal and external walls, however the use of this material as a facade covering has been increasingly studied due to the emergence of pathological manifestations, which cause several damages to the building. The present work aims to study the main pathologies existing in the ceramic tiles of the facade and discuss the possible causes that originated, as well as propose preventive measures. This study was divided into two stages: A literature review that sought to cover the contextualization of the ceramic coating and the main layers that comprise it, the execution process with its stages and the main functions. Soon afterwards to support the case study, a bibliographic study was also carried out on the pathologies existing in ceramic wall cladding. Subsequently, a case study was carried out in which site inspections were carried out and a questionnaire was applied to the person responsible for the construction of the Dix-Huit Rosado municipal theater. The case study showed that the main pathology detected on the theater facades was the detachment of the tablets, which in some way became generalized on the facades, unfortunately it is a serious pathology, since it can cause accidents in users who need to transit around the theater. The importance of preventive maintenance and testing in laboratories was verified to verify the causes that led to the loss of adherence of the tablets. However, due to all preventive measures against covid-19, it was not possible to carry out tests, but it would be relevant that other studies were carried out and that they could carry out on-site inspections and tests, in order to identify which problems/failures that led to the emergence of this anomaly
Keywords: Patologia; Revestimento cerâmico; Fachadas; Pathology; Ceramic tiles; Facades; ENGENHARIAS::ENGENHARIA CIVIL